Identifying and Classifying Spelling and Vocabulary Errors in English Language Learning: an Error Analysis Approach - Hendriyani, Hendriyani; Runggo, Yusniarti (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to identify and classify spelling and vocabulary errors made by students in the process of learning English. This study utilizes an error analysis approach to investigate students’ written work, emphasizing spelling and vocabulary errors. Methodology: This study utilizes an error analysis approach to investigate students’ written work, emphasizing spelling and vocabulary errors. This study uses a descriptive qualitative method to analyze students’ written assignments. Main Findings: The findings indicate that the most frequent writing errors involve prepositions and pronouns, each accounting for 0.04%, followed by article at 0.07%, and word choice at 0.09%. The most frequent writing error identified is related to spelling, accounting for 2.52%. The most common vocabulary-related writing error was punctuation, accounting for 6.78%, followed by subject-verb agreement at 0.45%. Errors in fragments and capitalization each made up 0.23%, while errors in the use of tenses (0.07%) and omissions (0.04%). Novelty/Originality of this study: The novelty of this research lies in its focus on two micro-linguistic aspects (spelling and vocabulary) that are rarely explored in previous studies. Using an error analysis approach, it identifies and categorizes students’ errors, offering practical insights and contributions to improving the teaching of academic English writing at the tertiary education level.